The Usborne book of kings & queens - Wingate, Philippa; Watton, Ross (Tulsa, OK : EDC Pub., 1995)
Looks at rulers throughout history, exploring their lives from coronations to funerals.
"From Tutankhamun to Elizabeth II"--Cover.
Includes index.
8.4
5-8
Keywords: Kings and rulers -- Biography -- Juvenile literature; Kings, queens, rulers, etc; Kings and rulers -- Biography; Queens -- Biography